A CRITICAL REVIEW OF INDONESIAN TRADITIONAL PROVERBS BY DERRIDA’S DECONSTRUCTION - Zakaria, Zakaria (English Review: Journal of English Education, 2024)
Abstrak:This research uses qualitative case studies with Derrida's deconstruction method. The object of research is the text of traditional Indonesian proverbs. The results of the research conclude that several mythical meanings of traditional Indonesian proverb texts can be shifted by another meanings, the analysis shows that the proverb of air beriak tanda tak dalam means someone who talks a lot without knowledge can be reconstructed with meaning “a person who talks a lot is a person with knowledge so it must be present as many arguments as possible.” The proverb of buah jatuh tak jauh dari pohonnya means parents and children have the same temperament and character, can also be reconstructed with meaning “that a child can be shaped by a good or bad environment, not just by the parents.” The proverb of hujan emas di negeri orang, lebih baik di negeri sendiri can be reconstructed also with the meaning of “it would be better live in someone else's country if it can give a guarantee of prosperity”. Finally, the proverb of biar lambat asal selamat can be reconstructed by some meaning based on considerations of effectiveness and efficiency of work. Meaning will continue to move and look for new traces of meaning, therefore meaning is never single and absolute but continue to be born along with each dimension of perspective.